2011
DOI: 10.1093/infdis/jir700
|View full text |Cite
|
Sign up to set email alerts
|

Semen of HIV-1–Infected Individuals: Local Shedding of Herpesviruses and Reprogrammed Cytokine Network

Abstract: HIV-1 infection results in an aberrant production of cytokines and reactivation of EBV and CMV that further changes the seminal cytokine network. The altered seminal milieu in HIV-1 infection may be a determinant of HIV-1 sexual transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 23 publications
10
80
1
5
Order By: Relevance
“…Notably, no significant differences were evident in any cytokine between patients and controls. When calculating the cytokine ratio between blood and semen, specific cytokine spectra were obvious, comparable to those reported for HIV patients and controls (Lisco et al, 2012). In addition, no significant correlations between blood levels of IL-6 and IL-10 and respective seminal concentrations were detected.…”
Section: Discussionsupporting
confidence: 72%
“…Notably, no significant differences were evident in any cytokine between patients and controls. When calculating the cytokine ratio between blood and semen, specific cytokine spectra were obvious, comparable to those reported for HIV patients and controls (Lisco et al, 2012). In addition, no significant correlations between blood levels of IL-6 and IL-10 and respective seminal concentrations were detected.…”
Section: Discussionsupporting
confidence: 72%
“…28,79,80 Several other immunologic factors are present in semen at remarkably high levels, including IL-7, TGF-b, and prostaglandins of E series (PGE). 76,81,82 These immune mediators have both pro-and antiinflammatory effects. Understanding the interaction of these various immunologic factors contained in seminal plasma with the genital mucosa has important implications for determining the impact of semen on mucosal propensity to HIV-1 infection.…”
Section: Seminal Plasma and Female Genital Tract Immune Responsementioning
confidence: 99%
“…In the seminal plasma of men infected with HIV, upregulation of specific subset of pro-inflammatory factors in the seminal plasma was demonstrated in several studies. 76,82,101 Furthermore, there is increased interaction between individual cytokines, resulting in 'cytokine networks' that may be less able to effectively respond to viral infection due to their heightened correlated activity. 101 In support of this, seminal plasma from HIV-positive men in the acute phase of infection has been reported to contain much higher concentrations of an array of pro-inflammatory cytokines and chemokines, as compared to uninfected or chronically infected samples.…”
Section: Sp Contains Abundant Immunomodulatory Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Berlier et al described a positive correlation with interleukin (IL)-1b, 15 while Storey et al described a positive correlation with RANTES, 16 and Sheth et al showed positive correlations with IL-6, IL-8, IL-12, and interferon (IFN)-c. 17 Furthermore, Lisco et al recently suggested that HIV-1 infection causes a ''reprogrammed cytokine network'' in the seminal plasma with elevated levels of several proinflammatory cytokines including IL-1a, IL-1b, IL-6, and IL-8, which do not correlate with blood plasma cytokine levels. 18 This suggests that cytokine expression is compartmentalized and that seminal plasma cytokines are likely produced within the male genital tract.…”
Section: Introductionmentioning
confidence: 99%